1996
DOI: 10.1210/jcem.81.4.8636359
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ability of bread versus bread plus meat to treat and prevent subsequent hypoglycemia in patients with insulin-dependent diabetes mellitus.

Abstract: We sought to determine whether treatment of hypoglycemia with a snack containing both protein and carbohydrate results in more prolonged protection against subsequent hypoglycemia than ingestion of carbohydrate alone. We studied six insulin-dependent diabetic subjects on two occasions. On both occasions subjects received a variable overnight insulin infusion to achieve euglycemia followed by a constant insulin infusion (approximately 0.5 mU x kg(-1) x min(-1)) designed to produce hypoglycemia. When glucose rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Evidence also links the low polyunsaturated to saturated fat ratio in meats, particularly red meats, to diabetes incidence [44] . More recent evidence also raises the possibility of a pathway where insulin resistance is produced from chronically elevated levels of glucagon and cortisol [11,12] -hormones that have been found to be associated with higher meat intake [13][14][15] . Our null findings for fish intake may have resulted from a protective effect caused from -3 fatty acids and are also consistent with studies indicating that those consuming fish are less likely to develop chemically induced diabetes [45,46] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also links the low polyunsaturated to saturated fat ratio in meats, particularly red meats, to diabetes incidence [44] . More recent evidence also raises the possibility of a pathway where insulin resistance is produced from chronically elevated levels of glucagon and cortisol [11,12] -hormones that have been found to be associated with higher meat intake [13][14][15] . Our null findings for fish intake may have resulted from a protective effect caused from -3 fatty acids and are also consistent with studies indicating that those consuming fish are less likely to develop chemically induced diabetes [45,46] .…”
Section: Discussionmentioning
confidence: 99%
“…More recent evidence also raises the possibility that some of the diet-diabetes relation is mediated through pathways related to chronic inflammation [10] or chronically elevated levels of glucagon and cortisol [11,12] . Furthermore, higher levels of these hormones have been found to be associated with animal product intake [13][14][15] . Interestingly, meat protein has been implicated in diabetic renal disease due to its effect on the glomerular filtration rate [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Including protein in the bedtime snack seems to provide better overnight protection from hypoglycemia than simple carbohydrates alone (62). However, one study in adults indicated that the addition of protein (bread with meat) did not give better protection against hypoglycemia 3 h after the snack (63). Extra slowly absorbed complex carbohydrate at bedtime may be helpful especially following strenuous exercise in the afternoon or evening (59, 64–67).…”
Section: Prevention Of Hypoglycemia – Special Considerationsmentioning
confidence: 99%
“…21,23,24 There is no clear consensus regarding the effect of protein on blood glucose levels in type 1 diabetes. 25,26 Therefore, protein ingestion is not recommended for the treatment or prevention of hypoglycemia.…”
Section: Do Protein and Fat Play A Role In Hypoglycemia Treatment?mentioning
confidence: 99%